2004
DOI: 10.1021/bi049524s
|View full text |Cite
|
Sign up to set email alerts
|

Cold Shock Domain of the Human Y-Box Protein YB-1. Backbone Dynamics and Equilibrium between the Native State and a Partially Unfolded State

Abstract: The three-dimensional structure of the central cold shock domain (CSD) of the human Y-box protein (YB-1 CSD) is virtually identical to those available for the bacterial cold shock proteins (Csp's). We have further characterized YB-1 CSD by studying its dynamics by nuclear magnetic resonance. The observed structural similarity is reflected in the backbone dynamics, which for YB-1 CSD is very similar to that of the Escherichia coli protein CspA. The rotational correlation time of YB-1 CSD shows that it is a mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
3
10
1
Order By: Relevance
“…One set is characteristic of disordered (unfolded) proteins with 1 H chemical shifts in a narrow range of ∼7.9–8.5 ppm, while the other is characteristic of folded proteins. This is consistent with the previous study ( 45 ). The result shows that this CSD construct exists in two conformations, one folded and one unfolded or disordered, which undergo slow conformational exchange in the NMR time regime.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…One set is characteristic of disordered (unfolded) proteins with 1 H chemical shifts in a narrow range of ∼7.9–8.5 ppm, while the other is characteristic of folded proteins. This is consistent with the previous study ( 45 ). The result shows that this CSD construct exists in two conformations, one folded and one unfolded or disordered, which undergo slow conformational exchange in the NMR time regime.…”
Section: Resultssupporting
confidence: 94%
“…Peak assignments of CSDex are labeled. For CSD (aa 51–129), the assignments were retrieved from the published data ( 45 ) and the residues from the unfolded form are indicated by appending ‘U’ in front of residue numbers. The peaks from the sidechains of W, Q and N are labeled by appending “s" after the residue numbers.…”
Section: Resultsmentioning
confidence: 99%
“…The YB-1 cold shock domain consists of five anti-parallel β-strands forming a β-barrel. The NMR analysis showed low stability of CSD that remains only 70% native at 25 °C [14]. This fact is also supported by microcalorimetry data.…”
Section: The Structure Of Yb Proteinssupporting
confidence: 69%
“…The CD spectrum of YB-1(Full) is similar to that of FRGY2 (Y-box protein from Xenopus laevis) 19 and YB-1 from Guryanov's group reported previously. 20 Although it has been reported that the CSD of YB-1 has an antiparallel b-barrel structure in only 95% H 2 O and 5% D 2 O solution, 21 our CD data showed that the domain had mainly random coils under the buffer conditions. The NMR relaxation measurements have demonstrated reportedly that the CSD exhibits an equilibrium between 70% folded and 30% unfolded states.…”
Section: Resultscontrasting
confidence: 68%